Genetic polymorphisms in the renin-angiotensin system and cognitive decline in Parkinson’s disease - Pierzchlińska, Anna (Mol Biol Rep, 2021)
BACKGROUND: Renin-angiotensin system (RAS) influences the central nervous system not only through its peripheral impact—the brain possesses its own local RAS. Studies showed altered RAS components in Parkinson’s disease (PD) and their association with oxidative stress which may be linked to neurodegeneration and dementia. Moreover, the protective functions of RAS blockade antagonists against cognitive decline and dementia have been suggested. This study aimed to examine whether genetic variability in RAS genes correlates with cognitive decline in PD. METHODS AND RESULTS: We genotyped single nucleotide polymorphisms (SNPs) in angiotensinogen (AGT: rs699, rs4762), angiotensin II receptors (AGTR1: rs5186 and AGTR2: rs5194, rs1403543) genes, as well as insertion/deletion polymorphism in the angiotensin-converting enzyme (ACE I/D) gene in 256 PD patients, divided into three groups: without cognitive decline, with mild cognitive impairment and with PD dementia. We did not find any significant differences in the frequencies of the analysed polymorphisms in any of the groups. CONCLUSIONS: Despite no direct correlation between the investigated polymorphisms in RAS genes and cognitive decline in PD, we believe the impact of those genotypes may be indirect, affecting RAS blockade treatment. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s11033-021-06569-6.